2009
DOI: 10.1007/s11242-009-9374-5
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Mobilization and Creeping Flow of Oil Slugs in a Water-Filled Capillary

Abstract: An experimental investigation was carried out on mobilization and very slow flow of oil slugs in a capillary tube. The pressure drop of the slug flow was measured at every stage of mobilizing and moving the oil slugs as a function of capillary number in the range of 4 × 10 −7 -6 × 10 −6 . The pressure drop across the oil slug experienced three stages: build-up, hold-up, and steady stages. During the build-up stage, the convex rear end of the slug was becoming concave into the oil slug and the convex front end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 31 publications
4
26
1
Order By: Relevance
“…When the number of edges goes to infinity, the polygon can be considered circular. Although the film between the nonwetting phase and the inner walls of the tube is extremely thin, the influence of the liquid membrane on two-phase flow is non-negligible, on the condition that the viscosities of the phases are unequal and the scale of the cross section of the tube is very small (Dai et al 2016;Dai and Wang 2014;Dai and Zhang 2013;Dong et al 2009;Fairbrother and Stubbs 1935;Taylor 1961). The influence of the film on the flow in the tubes with polygonal cross sections will be discussed in a later section.…”
Section: Equilateral Polygonmentioning
confidence: 99%
“…When the number of edges goes to infinity, the polygon can be considered circular. Although the film between the nonwetting phase and the inner walls of the tube is extremely thin, the influence of the liquid membrane on two-phase flow is non-negligible, on the condition that the viscosities of the phases are unequal and the scale of the cross section of the tube is very small (Dai et al 2016;Dai and Wang 2014;Dai and Zhang 2013;Dong et al 2009;Fairbrother and Stubbs 1935;Taylor 1961). The influence of the film on the flow in the tubes with polygonal cross sections will be discussed in a later section.…”
Section: Equilateral Polygonmentioning
confidence: 99%
“…In a later study, Schwartz et al [33] investigated the effect of viscosity, which was found to increase the film thickness, without affecting the dependence on Ca. Recently, an experimental investigation of a liquid slug has been reported by Dong et al [34], but no comparison with theoretical predictions has been provided. A possible interpretation of the discrepancy between theory and experiments is the presence of surface-active agents at the bubble or droplet interface.…”
Section: Axisymmetric Droplets Of Radius Much Larger Than Tube Radiusmentioning
confidence: 99%
“…In the efforts to reveal the mechanism, capillary models have been found to be useful. Experimental investigations on the mobilization of oil slugs in capillary models have been reported (Dong et al, 2009;Zhang and Dai, 2012). Recently, Dai and Zhang (2013) presented their findings of the presence and role of a water film in mobilizing an oil slug in a capillary model and some effects of the water film on the motion of the oil slug.…”
Section: Introductionmentioning
confidence: 99%